The Methodology of Tafsir Ishari and a Critical Analysis from the Perspective of Qur’anic Exegesis Studies - Mansur (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
Tafsir ishari represents one of the distinctive traditions within Qur'anic exegesis that seeks to uncover the inner spiritual meanings of Qur'anic verses beyond their apparent textual expressions. Although this interpretive approach has significantly contributed to the development of Islamic spirituality and Sufi thought, its methodological validity continues to generate scholarly debate due to concerns regarding subjectivity, epistemological legitimacy, and the absence of standardized interpretive procedures. This study aims to examine the conceptual foundations, methodological characteristics, and critical issues surrounding tafsir ishari from the perspective of contemporary Qur'anic exegesis studies. Employing a qualitative library research design with descriptive-analytical and critical approaches, the study analyzes classical and contemporary literature concerning Sufi exegesis, Qur'anic interpretation, and Islamic epistemology. The findings indicate that tafsir ishari functions primarily as an epistemological orientation that complements rather than replaces the outward (zahir) interpretation of the Qur'an. Its interpretive process is characterized by reliance on spiritual inspiration (ilham), symbolic interpretation, and ethical contemplation while maintaining consistency with the literal meaning of the text. Nevertheless, the study identifies three major methodological challenges, namely the absence of a standardized interpretive framework, the epistemological limitations of inspiration as a source of knowledge, and tensions between symbolic interpretation and established principles of Arabic linguistics. The study concludes that tafsir ishari should be understood as a valuable spiritual-hermeneutical tradition whose academic legitimacy depends upon maintaining methodological transparency, linguistic coherence, and epistemological accountability. This research contributes to contemporary Qur'anic exegesis by proposing a balanced analytical framework that integrates the spiritual richness of Sufi interpretation with the methodological rigor required in modern Qur'anic studies.